Teoretyczne podejście do świadomości jako kategorii interdyscyplinarnej – kilka refleksji - Ayzik, Elanit (Studia Edukacyjne, 2020)
The article presents different definitionsfrom different disciplines for the concept of “Awareness” and the central role of science in shaping the way teachers think and change their perceptions. In a period of the lack of stability, diversity, and heterogeneity in academic, cultural, and socioeconomic terms, teaching and education become a complicated and demanding tasks for the teacher. The teacher who meets the complex educational challenges findsit difficultto adjust to accelerated and endless social, scientific,and technological changes and to change the perception of his role from a source of knowledge to a transfer of knowledge. Most teachers of our time were not trained to be conscious of the influencesof globalization on the lives of the students and communities, differences, equality, and globalization that characterize society as a whole and are required of the teachers in society of our time. The author definesthe teachers’ consciousness as an Interdisciplinary Category. The increase of the teachers’ awareness of the processes of thinking and doing, as a result of the internal and external events around them, may help teachers map their abilities, needs, and expectations, understand the factors of their behavior, plan their course for the future, and definefor themselves goals commensurate with the requirements. The awareness grants the teachers an opportunity to take responsibility over the knowledge and thus may change the school experience.